2022
DOI: 10.1037/rep0000460
|View full text |Cite
|
Sign up to set email alerts
|

The RESCUE problem solving intervention for stroke caregivers: A mixed-methods pilot study.

Abstract: Purpose/Objective: Stroke caregivers face many challenges after a family member experiences stroke. Because caregivers play such a crucial role in health care, there is a need for more interventions in webbased formats that focus on caregiver psycho-education and skills building. A pilot study was devised to determine the feasibility, acceptability, and value of an active, 4-week telephone and web-based intervention for stroke caregivers. Method/Design: A one-group, pretest-posttest design with a mixed-methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Topics included in the training and discussion included education for stroke care, factsheets about strokes, after strokes, personality changes associated with strokes, rapport building strategies, communication techniques, fall prevention, and managing medicines to name a few of the covered topics. The identified interviews did show a promise for other web-based instruction as the individuals experienced a feasible intervention with valuable instruction that led to new strategies to relieve stress and to prioritize their health needs, however, the study showed no change in the problem-solving or health-related quality of life itself showed no change [14]. Denno et al [15] identified in a study conducted with 153 caregivers 18 years or older who cared for stroke survivors during a two-year period, that there was an increase in caregiver burden was associated with significantly poorer mental health of informal caregivers of stroke survivors with spasticity.…”
Section: Researchmentioning
confidence: 90%
See 2 more Smart Citations
“…Topics included in the training and discussion included education for stroke care, factsheets about strokes, after strokes, personality changes associated with strokes, rapport building strategies, communication techniques, fall prevention, and managing medicines to name a few of the covered topics. The identified interviews did show a promise for other web-based instruction as the individuals experienced a feasible intervention with valuable instruction that led to new strategies to relieve stress and to prioritize their health needs, however, the study showed no change in the problem-solving or health-related quality of life itself showed no change [14]. Denno et al [15] identified in a study conducted with 153 caregivers 18 years or older who cared for stroke survivors during a two-year period, that there was an increase in caregiver burden was associated with significantly poorer mental health of informal caregivers of stroke survivors with spasticity.…”
Section: Researchmentioning
confidence: 90%
“…A pilot study was devised by Jordan et al [14] to determine the feasibility, acceptability, and value of an active, 4-week telephone and web-based intervention for stroke caregivers. The study consisted of one group, who underwent pretest and posttest designs using a mixed-methods approach for online web-based training to evaluate problem-solving abilities and health-related quality of life topics.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation